Neutron Generation in CANDOR, an Advanced-Fuel Fusion Experiment. (17th November 2017) - Zucchetti, M.; Riva, M.; Testoni, R.; Candido, L.; Coppi, B.
Abstract: CANDOR is a high-field advanced fusion fuel cycle experiment based on Ignitor, but with larger dimensions and higher fusion power: it is a feasibility study of a high-field Deuterium-Helium-3 (D3He) experiment of larger dimensions and higher fusion power than Ignitor, still based on the core Ignitor technologies. Results of investigations on the feasibility of D3He burning and side neutrons production in D3He plasmas and specifically in CANDOR show that, with the initial use of DT triggering, the need for an intense auxiliary heating would be considerably alleviated. The total released 14 MeV neutron energy during the 16-second burning sums to about 210 MJ. DT and DD neutron currents incoming in the CANDOR plasma chamber wall and the Neutron Wall Loads have been computed. D3He ignition could be studied in CANDOR, with modest and conservative developments of the present technology. CANDOR has a low neutron wall loading, softer neutron spectrum, low radiation damage, and - consequently - lower neutron induced activation and radioactive inventory.